2006
DOI: 10.1007/bf02974274
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic constituents fromSolanum lyratum

Abstract: Activity-guided fractionation of the ethanol extract of the whole plant from Solanum lyratum resulted in the isolation of a new pregnane derivative glycoside, 16-dehydropregnenolone 3-O-alpha-L-rhamnopyranosyl-(1 --> 2)-beta-D-glucopyranosid uronic acid (2), as well as other six known compounds: 16-dehydropregnenolone (1), allopregenolone (3), protocatechuic acid (4), vanillic acid (5), caffeic acid (6), and scopoletin (7). The structures of the isolated compounds were elucidated on the basis of their spectral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…Compounds 1-6 and 8-13 were identified by comparing the 1 H-, 13 C-NMR, and MS spectra with the literature as 24-methylenecycloartanol (1) (De Pascual Teresa et al, 1986), p-hydroxybenzaldehyde (2) (Jang et al, 1990), ferulic acid (3) (He et al, 2005), p-coumaric acid (4) (Iiyama et al, 2008), vanillic acid (5) (Sun et al, 2006), β-D-(1-O-acetyl-3-O-trans-feruloyl)fructofuranosy-α-D-2',4',6'.-O-triacetyglucopyranoisde (6) (Xiong et al, 2008), β-D-(1-O-acetyl-3,6-O-trans-diferuloyl) fructofuranosyl-α-D-2',4',6'.-O-triacetylglucopyranoisde (8) (Osamu et al, 1996), hydroxytyrosol acetate (9) (Gordon et al, 2001), hydroxytyrosol (10) (Capasso et al, 1997), isorhamnetin-3-O-rutinoside (11) (Nakano et al, 1989), n-butyl-α-D-fructofuranoside (12) (Li et al, 2004), and n-butyl-β-D-fructopyranoside (13) (Zhang et al, 1996). Compounds 3 and 9-13 were isolated for the first time from this plant.…”
Section: Resultsmentioning
confidence: 99%
“…Compounds 1-6 and 8-13 were identified by comparing the 1 H-, 13 C-NMR, and MS spectra with the literature as 24-methylenecycloartanol (1) (De Pascual Teresa et al, 1986), p-hydroxybenzaldehyde (2) (Jang et al, 1990), ferulic acid (3) (He et al, 2005), p-coumaric acid (4) (Iiyama et al, 2008), vanillic acid (5) (Sun et al, 2006), β-D-(1-O-acetyl-3-O-trans-feruloyl)fructofuranosy-α-D-2',4',6'.-O-triacetyglucopyranoisde (6) (Xiong et al, 2008), β-D-(1-O-acetyl-3,6-O-trans-diferuloyl) fructofuranosyl-α-D-2',4',6'.-O-triacetylglucopyranoisde (8) (Osamu et al, 1996), hydroxytyrosol acetate (9) (Gordon et al, 2001), hydroxytyrosol (10) (Capasso et al, 1997), isorhamnetin-3-O-rutinoside (11) (Nakano et al, 1989), n-butyl-α-D-fructofuranoside (12) (Li et al, 2004), and n-butyl-β-D-fructopyranoside (13) (Zhang et al, 1996). Compounds 3 and 9-13 were isolated for the first time from this plant.…”
Section: Resultsmentioning
confidence: 99%
“…However, Solanum lyratum is commonly used for treatment of liver, lung esophagus cancer, and leukemia in the Chinese population [15, 16]. Many studies showed that Solanum lyratum extracts (SLE) inhibited proliferation in human hepatoma BEL-7402 cells, gastric carcinoma SGC-7901 cells, and melanoma A375-S2 cells in vitro and in vivo [16, 17]. SLE also triggered apoptosis in human cervical cancer HeLa cells through Fas/Fas ligand (FasL) expression [18] promoted the activity of protein kinase A (PKA) in the gastric cancer cells [19, 20] and provoked caspase-3-mediated apoptosis in human colon cancer colo 205 cells [21].…”
Section: Introductionmentioning
confidence: 99%
“…The other known compounds were identified as cedrol (4), 29) widdrol (5), 30) savinin (6), calocedrin (7), 31) 10-oxowiddrol (8), 30) 12-hydroxywiddrol (9), 32) (+)-naringenin (10), 33) vanillic acid methyl ester (11), 34) (+)-taxifolin (12), (+)-aromadendrin (13), 33) kaempferol (14), quercetin (15), 35) (7S,8R)-dihydro-3′-hydroxy-8-hydroxymethyl-7-(4-hydroxy-3-methoxyphenyl)-1′-benzofuranpropanol (16), 36) styraxlignolide C (17), 37) protocatechuic acid (18), vanillic acid (19), 38) (20), 27) and (+)-catechin (22) 39) on the basis of spectroscopic analysis, chemical evidence, and data from the literature. Although compounds 16 and 20 were previously reported from Santalum album 36) and Viburnum awabuki, 27) respectively, this is the first time they were isolated from J. chinensis.…”
Section: Resultsmentioning
confidence: 99%